Non-adherence with compression garment wear in adult burns patients: A systematic review and meta-ethnography. Issue 2 (March 2020) - Crofton, E.; Meredith, P.; Gray, P.; O'Reilly, S.; Strong, J.
Highlights: There are consistent themes relating to adherence to compression garment wear. The proposed model provides a comprehensive overview of the factors that may impact adherence to compression garment wear. Sensory factors, psychological state, functional impact, social support, choice, and education provided by therapists' impact adherence. Abstract: Objective: Up to 40% of adult burn-injured patients are non-adherent with prescribed compression garment wear. The aim of this paper is to systematically review the literature to understand barriers to adherence with compression garment wear. Method: Papers were included if they: investigated adults who required compression garment wear for the management of burns scars; focussed on reasons for non-adherence to compression garment wear; and were available in English. The process of meta-ethnography was then followed to synthesise the findings. Results: The factors impacting adherence to compression garment wear were grouped into six themes: sensory factors, psychological state, the impact of the garment on the patient's function, the availability of social support, the degree of choice, and the education provided to patients by their therapists. A model of compression garment adherence was developed detailing how these factors fit within the continuum of treatment for a burn-injured patient. Conclusions: Adherence to compression garment wear post-burn injury is a complex, dynamic phenomenon impacted by a range of factors. Findings from this review may inform approaches to support more consistent and/or extended garment wear, potentially improving scar outcomes and quality-of-life. Further research is recommended to investigate how each of the six identified themes impact adherence.